Desertion and the American soldier, 1776-2006 - Fantina, Robert (Algora Pub., 2006)
Despite the government's continued insistence on linking desertion with cowardice, the motivations for desertion are many and complex, and are either rooted in or encouraged by military policy. This history and analysis of military desertion from the Revolutionary War to Vietnam and the occupation of Iraq describes the official policies on desertion and how they have been implemented over time; problems in the military justice system; and the motivations for desertions. Comprehensive data and interviews with deserters are included.